1984
DOI: 10.1159/000110849
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Statistics in 515 Fatal Cases of Motor Neuron Disease

Abstract: In 515 cases of motor neuron disease followed until death, (1) the proportion of three subtypes of motor neuron disease (MND): amyotrophic lateral sclerosis (ALS), progressive bulbar paralysis (PBP), spinal progressive muscular atrophies (SPMA) was 78.3, 1.9, 19.8; (2) sex ratios were 1.41 in ALS, nearly one in PBP and 1.59 in SPMA, the ratio being high in cases initially involving the upper limbs; (3) age at onset was smoothly unimodal and identical in three subtypes; (4) bulbar symptoms appeared either at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Two large retrospective epidemiological studies have reported the presence of unspecified dementia in 4% and 6% of patients with MND,32 33 whereas two smaller prospective studies did not identify any demented patients 1214 Likewise, a large recent study of 146 patients under follow up by a specialist MND outpatient service seemed not to report any frankly demented patients despite finding evidence of more subtle cognitive impairment on neuropsychological assessment in a third of cases 17…”
Section: Discussionmentioning
confidence: 99%
“…Two large retrospective epidemiological studies have reported the presence of unspecified dementia in 4% and 6% of patients with MND,32 33 whereas two smaller prospective studies did not identify any demented patients 1214 Likewise, a large recent study of 146 patients under follow up by a specialist MND outpatient service seemed not to report any frankly demented patients despite finding evidence of more subtle cognitive impairment on neuropsychological assessment in a third of cases 17…”
Section: Discussionmentioning
confidence: 99%
“…Bulbar progressive paresis (bulbar onset) occurs in 25%–35% of patients, whereas 70%–81% of all forms will develop bulbar symptoms of dysarthria and dysphagia 9 , 26 , 28 , 29 . Symptoms of bulbar involvement begin with salivary pooling and dysarthria 30 .…”
Section: Risk Factors For Malnutrition In Amyotrophic Lateral Sclerosmentioning
confidence: 99%
“…In Amyotrophic Lateral Sclerosis/Motor Neurone Disease (ALS/MND) 50-70 % of patients ultimately experience bulbar symptoms such as dysphagia [4,11] so alternative methods of nutritional support are sought. In recent years, percutaneous endoscopic gastrostomy (PEG) feeding tubes have been proposed as an alternative to nasogastric tubes as a means of circumventing neurogenic dysphagia [15].…”
Section: Introductionmentioning
confidence: 99%